Socio Economic Conditions of the Tharu Community in Patihani VDC, Chitwan - Khaniya, Prem Raj (Tribhuvan University Journal, 2010)
The paper deals with the socio- economic conditions of the Tharu community in the Patihani VDC in Chitwan district. The paper is based on primary data for which a field survey was conducted in 2009. Questionnaire has been used as the major instrument for data collection. The total number of households covered in this study was 45. The heads of households were the respondents of this study. The study indicates that socio- economic conditions of the Tharus is gradually deteriorating.